Pablo: Pablo Chooses his Shoes: Level 1 (ELT Graded Reader) - Pitts,Sorrel (Ladybird Readers, 2022)
Ladybird Readers is an ELT graded reader series for children learning English as a foreign or second language. The series includes traditional tales, favourite characters, modern stories and non-fiction - featuring Spot, Peppa Pig and Peter Rabbit and classic authors such as Roald Dahl . Recommended for children aged 3-11, the eight levels of Ladybird Readers follow the CEFR framework(Pre-A1 to A2+) and include extra learning activities that develop key skills and provide preparation for the Cambridge English tests. Each book is Lexile measured and introduces key vocabulary and character names at the start of each reader. The books are written by language learning experts and include access to online audio, supplementary activities and learning resources including role plays, phrase cards and lesson plans.